Prevalence of seroconversion symptoms and relationship to set point viral load: Findings from a subtype C epidemic, 1995–2009 - Sullivan, Patrick S. (2012)
OBJECTIVE: To describe symptoms, physical exam findings, and set point viral load associated with acute HIV seroconversion in a heterosexual cohort of discordant couples in Zambia. DESIGN: We followed HIV serodiscordant couples in Lusaka, Zambia from 1995–2009 with HIV testing of negative partners and symptom inventories 3-monthly, and physical examinations annually. METHODS: We compared prevalence of self-reported or treated symptoms (malaria syndrome, chronic diarrhea, asthenia, night sweats, and oral candidiasis) and annual physical exam [PE] findings (unilateral or bilateral neck, axillary, or inguinal adenopathy; and dermatosis) in seroconverting versus HIV-negative or HIV-positive intervals, controlling for repeated observations, age, and sex. A composite score comprised of significant symptoms and PE findings predictive of seroconversion versus HIV-negative intervals was constructed. We modeled the relationship between number of symptoms and PE findings at seroconversion and log set-point viral load [VL] using linear regression. RESULTS: 2,388 HIV-negative partners were followed for a median of 18 months; 429 seroconversions occurred. Neither symptoms nor PE findings were reported for most seroconverters. Seroconversion was significantly associated with malaria syndrome among non-diarrheic patients (adjusted odds ratio [aOR]=4.0) night sweats (aOR=1.4), and bilateral axillary (aOR = 1.6), inguinal (aOR=2.2), and neck (aOR=2.2) adenopathy relative to HIV-negative intervals. Median number of symptoms was positively associated with set-point VL (p<0.001). CONCLUSIONS: Though most acute and early infections were asymptomatic, malaria syndrome was more common and more severe during seroconversion compared with HIV-negative and HIV-positive intervals. When present, symptoms and physical exam findings were non-specific and associated with higher set point viremia.